Er de alternative – de anderledes billeder? Groteske fremstillinger i de danske kalkmalerier: mod- eller medbilleder! - Christensen, Steen Schjødt (Hikuin, 2007)
Are they alternative – the different Images? Grotesque Imagery in the Danish Medieval Wall Paintings: anti- or Commentary Images! By Steen Schjødt Christensen Are they alternative the different images? And what does it mean that something is alternative or different? These are some of the questions evoked by a group of motifs in the Danish Medieval Wall paintings. The motifs are the so-called grotesque or antiiconography pictures. Images showing obscenities, mocking and grimacing faces, people dancing and demonstrating uncontrolled behaviour, fable-creatures and strange beings that seems to belong to a whole different world. These images form a neglected group of motifs – especially among art historians, since they are not properly registered in the existing iconographic indexes of Danish wall paintings. Above I have tried, to look at the motifs differently by indicating that they were not just characterized by negative meanings. This means that the grotesque and the sacred, the earthly and the heavenly were not always contrasts, but together formed a symbiosis within the world of Christian imagery. The grotesque images have traditionally been understood as symbols of the vices that are as moralising images contrasting the religious ones. But when seen in connection with the religious images it seems likely that the grotesques were part of interplay and not contrasting with the religious imagery. This was obvious in The Last Supper in Smørum where the secular and the religious images refer to the same things – that was the Eucharist and the Easter ceremonies. And as well in Nørre Herlev and Vigersted were games and juggling was not necessarily in contrast with the holy legend of St. Nicolas. And finally in Sæby church, where the open mouth was not negative, but on the contrary was a part of the propagation of Christian teachings. So perhaps the alternative images are not the different ones?